Identités en miroir : décryptage des prénoms Younes et Jonas dans « Ce que le jour doit à la nuit » - Yamina Taibi Maghraoui (Multilinguales)
This article delves into literary onomastics, focusing on the names "Younes" and "Jonas" in Yasmina Khadra’s "Ce que le jour doit à la nuit". It explores the main character’s experience of a torn identity, caught between two cultures, two origins, and two distinct ideologies. Our aim is to demonstrate how the protagonist perpetually engages in an identity quest through the names "Younes" and "Jonas", exacerbated by the political and social upheavals disrupting colonial Algeria. The intertwining of personal identity with broader socio-political changes becomes evident, unveiling the complexities arising from the protagonist’s cultural and territorial dualities.